The Development of web-based Cashier and Inventory Information Systems using Prototyping Model on Micro, Small, and Medium Enterprise (MSMEs) in Indonesia - Tan Andreas Dwi Pratama Subianto; Jansen Wiratama; Frans Ati Halim (Fakultas Ilmu Komputer, Universitas Dian Nuswantoro, 2023)
One example of information technology that has been widely applied to the business processes of a business venture is a web-based information system. Micro, Small, and Medium Enterprises (MSMEs) are productive businesses supporting the country's economy and individual companies. One of the MSMEs that will be the object of research this time is MSME Putra Anugrah Sejahtera, and This MSMEs sells premium spray paint for wheels with more than 100 colours. Around 15-20 customers daily make direct transactions at these MSMEs. In the running business processes, there are several obstacles, such as incorrect information when checking the stock of goods and recording sales transactions. This research aims to produce a web-based cashier and inventory information system to minimize errors and simplify sales and inventory transactions. System development using the Prototyping model with RDBMS MySQL was successfully developed. The results testing of systems using the User Acceptance Test (UAT) show that the resulting system follows user needs and answers the obstacles UMKM Putra Anugrah Sejahtera faces.